UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE PADA KELAS VII.E SMP NEGERI 4 LINTAU BUO - Isral, Isral (Jurnal Manajemen Pendidikan, 2018)
Based on the learning outcomes of Class VII.E students at SMP 4 Lintau Buo in Mathematics, it was found that student learning outcomes in Mathematics were still very low. The average student learning outcomes are still under the KKM. The purpose of this study was to describe and obtain information about efforts to improve student learning outcomes in Mathematics through the Think-Pair-Share (TPS) Type Cooperative Learning Model in Class VII.E 4 Lintau Public High School Buo Tanah Datar District. This research is a classroom action research. The procedure of research in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The subject of the study consisted of 21 students of Class VII.E of SMP 4 Lintau Buo. Research data was collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of the research and discussion that have been put forward, it can be concluded that the Cooperative Think-Pair-Share (TPS) Type Learning Model can improve student learning outcomes in Mathematics at Lintau Buo 4 Middle School. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle were 54.53 (sufficient), increasing to 83.93 (good) with an increase of 29.40%.